Massive right-sided hemorrhagic pleural effusion due to pancreatitis; a case report - Namazi, Mohammad Reza (BioMed Central, 2004)
BACKGROUND: Hemorrhagic pleural effusion, especially in the right hemithorax rarely occurs as the sole presentation of pancreatitis. CASE PRESENTATION: This article reports massive right-sided hemorrhagic pleural effusion as the sole manifestation of pancreatitis in a 16-year-old Iranian boy. The patient referred to Nemazee Hospital, the main hospital of southern Iran, with right-sided shoulder and chest pain accompanied with dyspnea. His chest x-ray showed massive right-sided pleural effusion. The pleural fluid amylase was markedly elevated (8840 U/L), higher than that in the serum (3318 U/L). Abdominal CT scan showed a cystic structure measuring about 5·2 cm in the head of pancreas, highly suggestive of a pancreatic pseudocyst. Pleural effusion resolved after 3 weeks of chest tube insertion but not completely. After this period of conservative therapy another CT scan showed that pseudocyst was still in the head of pancreas. So, external drainage was done with mushroom insertion and the patient was discharged after 40 days of hospitalization. The cause of pancreatitis could not be identified. CONCLUSION: Pancreatitis should be taken into consideration when hemorrhagic pleural effusion, especially in the right hemithorax occurs.